Creole discourse effects on the speech conjunctive system in expository texts - Clachar, Arlene (Journal of pragmatics, 2004)
The study illustrates how communicative patterns in the speech community and the degree of exposure to registers typical of written genres in home and out of school experiences are reflected in writing development through such pervasive but subconsciously selected language features as conjunctions. The structure of discourse in Creole cultures as well as the ramifications of an oral tradition were shown to have an effect on the Creole-speaking subjects’ tendency to draw on conjunctions and clause-linking strategies typical of registers of spoken discourse in their academic expository writing. On the contrary, the ESL subjects, from a literate tradition, exhibited fewer challenges than their Creole-speaking counterparts with respect to the transfer of the speech conjunctive system into the registers of written academic discourse. The study is guided by the sociocognitive notion that the social and cultural patterns of discourse are linked to the cognitive aspects of academic expository writing. As such, it demonstrates how the communicative patterns of the Creole speech community become pervasive in the development of expository writing. It also emphasizes the fact that the acquisition of these skills is shaped by the social and cultural environments in which they are embedded and are constructively viewed from these environments. Finally, the study provides the context for examining how Creole-speaking students, as opposed to ESL students, grapple with the unfamiliar registers of academic expository prose as they learn to distinguish the conjunctive system typical of registers of spoken discourse from that of registers appropriate for academic expository writing.